Cytogenetic abnormalities associated with reproductive failure in Pakistani population: experience of a tertiary care hospital - Faiza Naz,; Nazneen Perveen,; Syed Zulfiqar Ali Naqvi,; Sobia Rafiq, (Journal of the Pakistan Medical Association, 2024)
Constitutional chromosomal abnormalities play a significant role in causing reproductive anomalies in individuals of reproductive age. With the rapid advancement of genome engineering techniques, it has now become possible to cure different genetic disorders. However, very limited data is available regarding the prevalence of such aberrations in the Pakistani population. Considering this factor, this retrospective analysis was undertaken to elucidate the type and prevalence rate of such abnormalities in our population. A total of 241 individuals, who were referred to the Liaquat National Hospital, from January 2017 to December 2021, with a history of infertility or miscarriages, were evaluated using the standard GTG banding technique. The results revealed a notably high percentage 44(18.2%) of chromosomal abnormalities in our population. Surprisingly, the frequency of these anomalies was observed to be higher in males than in females. ---Continue